2019
DOI: 10.1108/jpbm-10-2018-2054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of user manual quality on customer satisfaction: the mediating effect of perceived product quality

Abstract: Purpose The purpose of this paper is to investigate the elements of user manual quality and its influences on perceived product quality and customer satisfaction in an integrated model structure. Design/methodology/approach Survey method was used to evaluate user manual quality and its influences on perceived product quality and customer satisfaction. Electrical appliances consumers were chosen in our sample. Factor analysis and structural equation modeling were performed to introduce, test and validate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 89 publications
2
38
0
1
Order By: Relevance
“…Data collected for all variables use a five-point Likert scale from Strongly Disagree (1) to Strongly Agree (5). The items of product quality are adapted from Gök et al (2019) and Xu et al (2017). It consists of eight items with Cronbach's alpha of 0,884.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected for all variables use a five-point Likert scale from Strongly Disagree (1) to Strongly Agree (5). The items of product quality are adapted from Gök et al (2019) and Xu et al (2017). It consists of eight items with Cronbach's alpha of 0,884.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the company will have the ability to survive in the long run. In a simple sense, the product quality is a product or service that can meet consumers' needs explicitly and implicitly (Armstrong & Kotler, 2015), product excellence perceived by consumers (Gök, Ersoy, & Börühan, 2019), and overall evaluation of a product by customers (Xu, Blankson, & Prybutok, 2017).…”
Section: N P R E S Smentioning
confidence: 99%
“…Over the time, the quality of a physical product was prioritized in the research of Calantone and Knight (2000) ; Cho and Pucik (2005) ; Forker et al (1996) ; Martínez-Costa et al (2009) ; Molina-Castillo et al (2013) ; Morgan and Vorhies (2001) and Prajogo and Sohal (2004) . Very recently, Kotler and Armstrong (2018) ; Lin et al (2018) and Gök et al (2019) also studied product quality.…”
Section: Literaturementioning
confidence: 99%
“…He also added that customer-oriented and product-selling firms practice quality and persuade consumer satisfaction. Lin et al (2018) and Gök et al (2019) found that product quality is a strong antecedent of customer satisfaction. Gök et al (2019) stated that contrast theory explains the clarification of the product evaluation process and the quality of the product that customer magnifies the gap between the product received and the product expected.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation